Meth Mouth-A Growing Epidemic in Dentistry? - Andreas Pabst; Juan Carlos Castillo-Duque; Axel Mayer; Marcus Klinghuber; Richard Werkmeister (MDPI AG, 2017)
In the past two decades, the synthetic style and fashion drug "crystal meth" ("crystal", "meth"), chemically representing the crystalline form of the methamphetamine hydrochloride, has become more and more popular in the United States, in Eastern Europe, and just recently in Central and Western Europe. "Meth" is cheap, easy to synthesize and to market, and has an extremely high potential for abuse and dependence. As a strong sympathomimetic, "meth" has the potency to switch off hunger, fatigue and, pain while simultaneously increasing physical and mental performance. The most relevant side effects are heart and circulatory complaints, severe psychotic attacks, personality changes, and progressive neurodegeneration. Another effect is "meth mouth", defined as serious tooth and oral health damage after long-standing "meth" abuse; this condition may become increasingly relevant in dentistry and oral- and maxillofacial surgery. There might be an association between general methamphetamine abuse and the development of osteonecrosis, similar to the medication-related osteonecrosis of the jaws (MRONJ). Several case reports concerning "meth" patients after tooth extractions or oral surgery have presented clinical pictures similar to MRONJ. This overview summarizes the most relevant aspect concerning "crystal meth" abuse and "meth mouth".